Friday

May 6, 2016
Total # Posts: 2,112

**Algebra**

Remark : ( a - b ) ^ 2 = a ^ 2 - 2 * a * b + b ^ 2
*May 20, 2012*

**Algebra**

sqrt ( x ) + 3 = sqrt ( x + 12 ) Subtract 3 from both sides: sqrt ( x ) + 3 - 3 = sqrt ( x + 12 ) - 3 sqrt ( x ) = sqrt ( x + 12 ) - 3 Square both sides : [ sqrt ( x ) ] ^ 2 = [ sqrt ( x + 12 ) ] ^ 2 - 2 * sqrt ( x + 12 ) * 3 + 3 ^ 2 x = x + 12 - 6 sqrt ( x + 12 ) + 9 x = x - ...
*May 20, 2012*

**Math**

Most useful form of straight-line equations is the "slope-intercept" form: y = m x + b This is called the slope-intercept form because "m" is the slope and "b" gives the y - intercept y - intercept = value of y when x = 0 In this case : y = x + 2 ...
*May 20, 2012*

**calculus**

x = first number y = second number x + y = 100 y = 100 - x P = x * y P = x * ( 100 - x ) P = 100 x - x ^ 2
*May 20, 2012*

**calculus**

x = width y = length P = Perimeter A = Area Perimeter = 2 * width + 2 * length P = 2 x + 2 y P = 2 * ( x + y ) 2 * ( x + y ) = 10 Divibe both sides by 2 x + y = 5 y = 5 - x Area = width * length A = x * y A = x * ( 5 - x ) A = 5 x - x ^ 2
*May 20, 2012*

**MATH**

n * log ( a ) = log ( a ^ n ) log ( a ) + log ( b ) = log ( a * b ) log ( a ) - log ( b ) = log ( a / b ) 2 log ( 3 ) = log ( 3 ^ 2 ) = log ( 9 ) 2 log ( 2 ) = log ( 2 ^ 2 ) = log ( 4 ) 2 log ( 3 ) - log ( 5 ) + 2 log ( 2 ) = log ( 3 ^ 2 * 2 ^ 2 / 5 ) = log ( 9 * 4 / 5 ) = log...
*May 20, 2012*

**math**

csc ^ 2 ( x ) - csc ( x ) + 9 = 11 Subtract 11 to both sides csc ^ 2 ( x ) - csc ( x ) + 9 - 11 = 11 - 11 csc ^ 2 ( x ) - csc ( x ) - 2 = 0 Substitute : csc ( x ) = u u ^ 2 - u - 2 = 0 The exact solutions are : u = - 1 and u = 2 u = csc ( x ) so : csc ( x ) = - 1 and csc ( x...
*May 19, 2012*

**algebra 2**

- 10
*May 17, 2012*

**math**

13 / 8 = ( 8 + 5 ) / 8 = 8 / 8 + 5 / 8 = 1 5 / 8 = 1.625
*May 17, 2012*

**trig**

Yes
*May 17, 2012*

**trig**

Corection: sin ( x ) = 1 / 2 sin ( x ) = - 1
*May 17, 2012*

**trig**

cos ^ 2 ( x ) = 1 - sin ^ 2 ( x ) 2 cos ^ 2 ( x ) - sin ( x ) = 1 2 * [ 1 - sin ^ 2 ( x ) ] - sin ( x ) = 1 2 - 2 sin ^ 2 ( x ) - sin ( x ) = 1 Subtract 1 to both sides 2 - 2 sin ^ 2 ( x ) - sin ( x ) - 1 = 1 - 1 - 2 sin ^ 2 ( x ) - sin ( x ) + 1 = 0 Substitute : sin ( x ) = u...
*May 17, 2012*

**math**

If your expression mean : 6 cos ^ 2 ( x ) + cos ( x ) = 1 then 6 cos ^ 2 ( x ) + cos ( x ) = 1 Subtract 1 to both sides 6 cos ^ 2 ( x ) + cos ( x ) - 1 = 1 - 1 6 cos ^ 2 ( x ) + cos ( x ) - 1 = 0 Substitute : cos ( x ) = u 6 u ^ 2 + u - 1 = 0 The exact solution are : u = - 1...
*May 17, 2012*

**Algebra 1a**

1750 / 0.06 = 29,166.6666 29,167 $
*May 16, 2012*

**Algebra**

- 4 ( t + 7 ) - ( t + 6 ) = 10 - 4 * t - 4 * 7 - t -+ 6 = 10 - 4 t - 28 - t - 6 = 10 - 5 t - 34 = 10 Add 34 to both sides - 5 t - 34 + 34 = 10 + 34 - 5 t = 44 divide both sides by - 5 t = - 44 / 5 = - 8.8 - 4 ( t + 7 ) - ( t + 6 ) = 10 - 4 ( - 8.8 + 7 ) - ( - 8.8 + 6 ) = 10 - ...
*May 16, 2012*

**algebra**

y ^ 7 / z ^3 = y ^ 4 * y ^ 3 / z ^ 3 = y ^ 4 * ( y / z ) ^ 3
*May 14, 2012*

**math**

Type this question in google. When you see list of results go on : a n s w e r s . y a h o o . com › ... › Physics
*May 13, 2012*

**math**

4.1 % = 4.1 / 100 = 0.041 104.1 % = 1 + 0.041 = 1.041 32.4 / 1.041 = 31.123 milion
*May 13, 2012*

**math**

In google type: quadratic equation online When you see list of results click on: Free Online Quadratic Equation Solver:Solve by Quadratic Formula When page be open in rectangle type: x^2+x+3=0 and click option: solve it You will see solution step-by step
*May 13, 2012*

**math**

4 x - y = 7 Add y to both sides 4 x - y + y = 7 + y 4 x = y + 7 Subtract 7 to both sides 4 x - 7 = y + 7 - 7 4 x - 7 = y y = 4 x - 7 5 x + y = 20 5 x + 4 x - 7 = 20 9 x - 7 = 20 Add 7 to both sides 9 x - 7 + 7 = 20 + 7 9 x = 27 Divide both sides by 9 9 x / 9 = 27 / 9 x = 3 y...
*May 13, 2012*

**geometry**

( 4 / 3 ) * 12 = 48 / 3 = 16
*May 13, 2012*

**geometry**

If the similarity ratio of two similar triangles is a : b, then the ratio of their areas is : a ^ 2 / b ^ 2 So : a ^ 2 / b ^ 2 = 36 / 25 a / b = sqrt ( 36 ) / sqrt ( 25 ) = 6 / 5
*May 13, 2012*

**Math**

1 ) The domain of a function is the set of all possible input values , which allows the function formula to work. The denominator of any fraction cannot have the value zero. I this case : x + 3 must be different of zero x different of - 3 Domain: ( - infinity , - 3 ) U ( - 3...
*May 13, 2012*

**math**

Use calculator on your computer start -> Programs -> Accessories -> Calculator When you open Calculator click View then Sceintific 10 ^ 1.27 = 18.620871366628674486717789978037
*May 12, 2012*

**functions**

1 h = 3600 s 4.3 pi * 3600 = 15480 pi rad / h 1 rotation = 2 pi radians 15480 pi / 2 pi = 7740 rotations / h
*May 12, 2012*

**math**

Circumference of a circle C = 2 r pi the arc length L = 2 r pi * theta / 360 ° = r * pi * theta / 180° 10 = r pi * 80 / 180 Multiply both sides by 180 10 * 180 = r * pi * 80 1800 = r * pi * 80 Divide both sides by 80 pi 1800 / 80 pi = r r = 1800 / 80 pi r = 40 * 45...
*May 12, 2012*

**math**

5 ( 2 z - 1) - 4 ( z + 9 ) = 4 ( z + 1 ) = 5 * 2 z - 5 * 1 - 4 * z - 4 * 9 = 4 * z + 4 * 1 10 z - 5 - 4 z - 36 = 4 z + 4 6 z - 41 = 4 z + 4 Subtract 4 z to both sides 6 z - 41 - 4 z = 4 z + 4 - 4 z 2 z - 41 = 4 Add 41 to both sides 2 z - 41 + 41 = 4 + 41 2 z = 45
*May 11, 2012*

**math**

¡Ü mean less or equal
*May 11, 2012*

**math**

4 x - 5 ¡Ü 2( x - 7 ) 4 x - 5 ¡Ü 2 * x - 2 * 7 4 x - 5 ¡Ü 2 x - 14 Add - 2 x to both sides 4 x - 2 x - 5 ¡Ü 2 x - 14 - 2 x 2 x - 5 ¡Ü - 14 Add 5 to both sides 2 x - 5 + 5 ¡Ü - 14 + 5 2 x ¡Ü - 9 Divide...
*May 11, 2012*

**trig**

cos ( pi - x )= - cos x
*May 11, 2012*

**math**

3 x ^ 2 - 5 = 0 Add 5 to both sides 3 x ^ 2 - 5 + 5 = 0 + 5 3 x ^ 2 = 5 Divide both sides by 3 x ^ 2 = 5 / 3 x = + OR - sqrt ( 5 / 3 ) 2 solutions : x = sqrt ( 5 / 3 ) and - sqrt ( 5 / 3 )
*May 10, 2012*

**Math**

( 3 x - 1 ) ^ -5 = 1 / ( 3 x -1 ) ^ 5 ( 3x - 1 ) ^ - 4 = 1 / ( 3 x -1 ) ^ 4 - 12 ( 3 x -1 ) ^ - 5 * ( 6 x + 7 ) ^ 5 + 30 ( 3 x - 1 ) ^ - 4 * ( 6 x + 7) ^ 4 = [ - 12 ( 6 x + 7 ) ^ 5 ) + 30 * ( 3 x - 1 ) * ( 6 x + 7 ) ^ 4 ] / ( 3 x - 1 ) ^ 5 = 6 * ( 6 x + 7 ) ^ 4 * [ ( - 2...
*May 9, 2012*

**math**

y = - 4 * 2 - 5 y = - 8 - 5 y = - 13
*May 9, 2012*

**math**

( a - b ) ^ 2 = a ^ 2 - 2 a b + b ^ 2 ( 8 - 0.02 ) ^ 2 = 8 ^ 2 - 2 * 8 * 0.02 + 0.02 ^ 2 = 64 - 0.32 + 0.0004 = 63.6804 2 + 8.3 * 0.4 = 2 + 3.32 = 5.32 ( 8 - 0.02 ) ^ 2 / ( 2 + 8.3 * 0.4 ) = 63.6804 / 5.32 = 11,97
*May 9, 2012*

**algebra 2**

In google type: quadratic equation online When you see list of results click on: Free Online Quadratic Equation Solver:Solve by Quadratic Formula When page be open click option : Solve by Completing the Square Then in rectangle type: x^2-4x-32=0 and click option: solve it You ...
*May 9, 2012*

**Maths**

When we have a two digit number, it can be expressed as : 10 a + b In this case : 10 a + b = orginal number The sum of the 2 digits is 15 a + b = 15 Subtract a to both sides a - a + b = 15 - a b = 15 - a If you reverse the digits of 10 a + b, it will be : 10 b + a 10 b + a = ...
*May 8, 2012*

**PHYSICS**

If MTR mean metre and mm mean millimeter, and if you want to find mass then : 1 m = 100 cm 1 cm = 10 mm 1 mm = 1 / 10 = 0.1 cm V = 100 * 100 * 4 * 0.1 = 4000 cm ^ 3 m = V * rho = 4000 * 1.056 = 4224 g 1 kg = 1000 g 4224 g = 4.224 kg Greek letter rho = density
*May 8, 2012*

**math HELP**

When the ball hits the ground height be zero. 25 t - 16 t ^ 2 = 0 t ( 25 - 16 t ) = 0 This equation will be zero when t = 0 OR 25 - 16 t = 0 25 - 16 t = 0 Add 16 to both sides 25 - 16 t + 16 t = 0 + 16 t 25 = 16 t Divide both sides by 16 25 / 16 = t t = 25 / 16 When t = 0 ball...
*May 8, 2012*

**Algebra 2**

A circle is the set of all points that are the same distance, r, from a fixed point. General Formula: x ^ 2 + y ^ 2 = r ^ 2 where r is the radius In this case : x ^ 2 + y ^ 2 = 25 = 5 ^ 2 The circle has a center of (0,0) and a radius of 5 x - y = 2 x - 2 = y y = x - 2 The ...
*May 8, 2012*

**Alg2**

- 3 x + z = - 3 Add 3 x to both sides - 3 x + 3 x + z = - 3 + 3 x z = 3 x - 3 x - 2 y - 3 z = - 5 x - 2 y - 3 * ( 3 x - 3 ) = - 5 x - 2 y - 3 * 3 x - 3 * ( - 3 = - 5 x - 2 y - 9 x + 9 = - 5 - 8 x - 2 y + 9 = - 5 Add 8 x - 9 to both sides - 8 x - 2 y + 9 + 8 x - 9 = - 5 + 8 x...
*May 8, 2012*

**Math B/C**

( a - b ) ^ 4 = a ^ 4 - 4 a ^ 3 b + 6 a ^ 2 b ^ 2 - 4 a b ^ 3 + b ^ 4 ( x - 45 ) ^ 4 = x ^ 4 - 4 * x ^ 3 * 45 + 6 * x ^ 2 * 45 ^ 2 - 4 * x * 45 ^ 3 + 45 ^ 4 = x ^ 4 - 4 * 45 * x ^ 3 + 6 * 2,025 * x ^ 2 - 4 * 91,125 + 4,100,625 x ^ 4 - 180 x ^ 3 + 12,500 x ^ 2 - 364,500 x + 4,...
*May 8, 2012*

**math**

Parabola 25 x ^ 2 = 64 + 16 y 25 x ^ 2 - 64 = 16 y Divide both sides by 16 25 x ^ 2 / 16 - 64 / 16 = y y = 25 x ^ 2 / 16 - 4 Quadratic equation. A parabola is an equation of the form y = a x ^ 2 + b x + c
*May 7, 2012*

**Functions-Math**

In google type : 2x^3+9x^2+kx-15 is divided by x+5, the remainder is 0 When you see list of results click on Y a h o o! Canada Answers - Polynomial Division Problem? You will see solution with explanation.
*May 7, 2012*

**Algebra 2**

4 b y - 3 b z + 8 d y - 6 d z = y ( 4 b + 8 d ) + z ( - 3 b - 6 d ) = y [ ( 4 ( b + 2 d ) ] + z [ ( - 3 ) ( b + 2 d ) ] = 4 y ( b + 2 d ) - 3 z ( b + 2 d) = ( b + 2 d ) ( 4 y - 3 z ) Answer c)
*May 7, 2012*

**Algebra 2**

If your expression mean : third root ( 3 x + 5 ) + 4 = 0 then third root ( 3 x + 5 ) = - 4 3 x + 5 = - 4 ^ 3 3 x + 5 = - 64 3 x = - 64 - 5 3 x = - 69 Divide both sides by 3 x = - 69 / 3 x = - 23
*May 7, 2012*

**Algebra 2**

third root ( 3 x ) + 5 + 4 = 0 third root ( 3 x ) + 9 = 0 third root ( 3 x ) = - 9 93 x = - 9 ^ 3 3 x = - 729 Divide both sides by 3 x = - 729 / 3 x = - 243
*May 7, 2012*

**Math**

( a + b ) ( a - b ) = a ^ 2 - b ^ 2 [ sqrt ( 10 ) + 3 ] [ sqrt ( 10 ) - 3 ] = sqrt ( 10 ) ^ 2 - 3 ^ 2 = 10 - 9 = 1 If your expression mean : sqrt [ ( 10 ) + 3 ] sqrt [ ( 10 ) - 3 ] then sqrt [ ( 10 ) + 3 ] sqrt [ ( 10 ) - 3 ] = sqrt ( 13 ) sqrt ( 7 ) = sqrt ( 13 * 7 ) = sqrt...
*May 7, 2012*

**Math**

1 / 100 = x / 225 1 * 225 = x * 100 225 = 100 x Divide both sides by 100 225 / 100 = x x = 2.25 Or simply : 225 / 100 = 2.25
*May 7, 2012*

**6th Grade Math**

If youe exspression mean : (9 / 2 ) x - 8 = - 5.5 + 4 x Multiply both sides by 2 2 * ( 9 / 2 ) x - 2 * 8 = 2 * ( - 5.5 ) + 2 * 4 x 9 x - 16 = - 11 + 8 x Subtract 8 x to both sides 9 x - 16 - 8 x = - 11 + 8 x - 8 x 9 x - 8 x - 16 = - 11 x - 16 = - 11 Add 16 to both sides x - 16...
*May 7, 2012*

**algebra**

If you expression mean : ( x - 3 ) ( x - 5 ) ( x - 7 ) = 0 The "Zero Product Property" says: If ( x - 3 ) ( x - 5 ) ( x - 7 ) = 0 then ( x - 3 ) = 0 or ( x - 5 ) = 0 or ( x - 7 ) = 0 Solutions : x = 3 x = 5 and x = 7
*May 6, 2012*

**algebra**

In google type: function graphs online When you see list of results click on: rechneronline.de/function-graphs When page be open in blue rectacangle type: x^2-4x+3 Then click option Draw Solutions : x = 1 and x = 3
*May 6, 2012*

**MATH**

ap = 2 ( p + 5 ) a1 = 2 ( 1 + 5 ) = 2 * 6 = 12 a2 = 2 ( 2 + 5 ) = 2 * 7 = 14 s3 = 2 ( 3 + 5 ) = 2 * 8 = 16 a4 = 2 ( 4 + 5 ) = 2 * 9 = 18 a5 = 2 ( 5 + 5 ) = 2 * 10 = 20
*May 6, 2012*

**Calc**

Go on : wolframalpha dot com When page be open in rectangle type: integrate dP/dt = 0.5(800-P) and click option = When you see result click option: Show steps
*May 6, 2012*

**Algebra**

2 / 3 - 4 / 5 - ( - 11 / 15 ) + 7 / 10 - 5 / 2 = 2 / 3 - 4 / 5 + 11 / 15 + 7 / 10 - 5 / 2 ______________________________________ Least Common factor = 30 2 / 3 = 20 / 30 4 / 5 = 4 * 6 / ( 5 * 6 ) = 24 / 30 11 / 15 = 2 * 11 / ( 2 * 15 ) = 22 / 30 7 / 10 = 3 * 7 / ( 3 * 10 ) = ...
*May 5, 2012*

**Math**

Circumference : C = 2 r pi C = 2 r pi Divide both sides by 2 pi C / 2 pi = r r = C / 2 pi r = 37.68 / ( 2 * 3.14 = r = 37.68 / 6.28 r = 6 cm Area: A = 4 r ^ 2 pi A = 4 * 6 ^ 2 * pi A = 4 * 36 * pi A = 144 pi A = 144 * 3.14 A = 452.16 cm ^ 2
*May 5, 2012*

**math**

1 / x + 3 / x ^ 2 = - 1 Multiply both sides by x ^ 2 x ^ 2 * 1 / x + 3 * x ^ 2 / x ^ 2 = - x ^ 2 x + 3 = - x ^ 2 x ^ 2 + x + 3 = 0 In google type: quadratic equation online When you see list of results click on: Free Online Quadratic Equation Solver:Solve by Quadratic Formula ...
*May 5, 2012*

**math**

In google type: quadratic equation online When you see list of results click on: Free Online Quadratic Equation Solver:Solve by Quadratic Formula When page be open in rectangle type: 6x^2+12x+5=0 and click option: solve it You will see solution step-by step
*May 5, 2012*

**math**

| x - 4 |-| 7 - x | = 1 | x - 4 | = 1 + | 7 - x | Eliminate the absolute values: First equation : ( - ( x - 4 ) ) = ( 7 - x ) + 1 Second equation : ( x - 4 ) = ( 7 - x ) + 1 Third equation : ( x - 4 ) = ( - ( 7 - x ) ) + 1 Fourth equation : ( x - 4 ) = ( 7 - x ) + 1 You have ...
*May 5, 2012*

**Math - patterns**

Prime numbers sequensce. A prime number is a natural number greater than 1 that has no positive divisors other than 1 and itself. 2 , 3 , 5 , 7 , 11 , 13 , 17
*May 4, 2012*

**math models**

1 ft = 12 in 1 ft ^ 2 = 12 ^ 2 = 144 in ^ 2 Areaa od a kitchen Ak = 20 * 16 = 320 ft ^ 2 Ak = 320 ft ^ 2 = 320 * 144 = 46,080 in ^ 2 Area of tiles At = 6 * 6 = 36 in ^ 2 Numbers of a tiles n = Ak / At n = 46,080 / 36 = 1280 OR 20 ft = 20 * 12 = 240 in One side of tiles = 6 in ...
*May 4, 2012*

**Math**

2 / x = 3 * 2 / 3 x = 6 / 3 x 5 / 3 x + 2 / x = 5 / 3 x + 6 / 3 x = 11 / 3x Answer is ( C )
*May 4, 2012*

**math**

f ( 0 ) = 3 * 0 ^ 2 - 4 * 0 = 3 * 0 + 0 = 0 + 0 = 0 f ( - 1 ) = 3 * ( - 1 ) ^ 2 - 4 * ( - 1 ) = 3 * 1 + 4 = 3 + 4 = 7 f ( 2 ) = 3 * 2 ^ 2 - 4 * 2 = 3 * 4 - 4 * 2 = 12 - 8 = 4
*May 4, 2012*

**Calculus**

second derivative is derivative of first derivative on wolframalpha dot com type : derivative 4 ( x - 3 ) / [ 2 x ^ 2 - 12 x + ( y -10 ) y ] and click option = then Show steps
*May 4, 2012*

**Calculus**

Go on: wolframalpha dot com When page be open in rectangle type: derivative ln (2X^2 - 12X + Y^2 -10Y) and click option = After a few seconds , when you see result click option: Show steps
*May 4, 2012*

**algebra**

b / 3 + 6 = 82 Subtract 6 from both side b / 3 + 6 - 6 = 82 - 6 b / 3 = 76 Multiply both sides by 3 3 * b / 3 = 3 * 76 b = 228
*May 4, 2012*

**algebra**

( - 7 x ^ 2 + 5 x - 9 ) - ( 2 x ^ 2 + 7 x + 5 ) = - 7 x ^ 2 - 2 x ^ 2 + 5 x - 7 x - 9 - 5 = - 9 x ^ 2 - 2 x - 14
*May 3, 2012*

**math**

sqrt ( x ^ 5 ) = ( x ^ 5 ) ^ ( 1 / 2 ) = x ^ ( 5 / 2 ) sqrt ( x ^ 2 ) = x = x ^ 1 = x ^ ( 2 / 2 ) 1 / sqrt ( x ^ 2 ) = x ^ ( - 2 / 2 ) sqrt ( x ^ 5 ) / sqrt ( x ^ 2 ) = sqrt ( x ^ 5 ) * 1 / sqrt ( x ^ 2 ) x ^ a * x ^ b = x ^ ( a + b ) x ^ ( 5 / 2 ) * x ^ ( - 2 / 2 ) = x ^ [ 5...
*May 3, 2012*

**help plz math**

ln ( a ) - ln ( b ) = ln ( a / b ) ln ( 3 x + 5 ) - ln ( 4 ) = ln [ ( 3 x + 5 ) / 4 ] ln ( 3 x + 5 )- ln ( 4 ) = ln [ ( 3 x + 5 ) / 4 ] = ln ( x + 1 ) Cancel logarithms by taking exp of both sides ( 3 x + 5 ) / 4 = x - 1 Multiply both sides by 4 3 x + 5 = 4 * ( x - 1 ) 3 x + 5...
*May 3, 2012*

**Math**

18 x ^ 5 + 3 x ^ 3 + 6 x = 3 x ( 6 x ^ 4 + x ^ 2 + 2 ) ( 18 x ^ 5 + 3 x ^ 3 + 6 x ) / 3 x = 3 x ( 6 x ^ 4 + x ^ 2 + 2 ) / 3 x = ( 3 x / 3 x ) ( 6 x ^ 4 + x ^ 2 + 2 ) = 1 * ( 6 x ^ 4 + x ^ 2 + 2 ) = 6 x ^ 4 + x ^ 2 + 2
*May 2, 2012*

**Math**

( 4 x ^ 2 - 5 x + 7 ) + ( x ^ 2 - 3 x - 6 ) = 4 x ^ 2 + x ^ 2 - 5 x - 3 x + 7 - 6 = 5 x ^ 2 - 8 x + 1
*May 2, 2012*

**Math**

a ) ( 2 x + 5 )( 2 x - 5 ) = 2 x * 2 x + 2 x * 5 - 5 * 2 x - 5 * 5 = 4 x ^ 2 + 10 x - 10 x - 25 = 4 x ^ 2 - 25
*May 2, 2012*

**Math**

x ^ 2 - 7 x y + 2 - ( 2 x ^ 2 + 3 x y - 6 ) = x ^ 2 - 2 x ^ 2 - 7 x y - 3 x y + 2 - ( - 6 ) = - x ^ 2 - 10 x y + 2 + 6 = - x ^ 2 - 10 x y + 8
*May 2, 2012*

**Calculus**

Go on: wolframalpha dot com When page be open in rectangle type: integrate square root (x)+e^-3x dx and click option = When you see result click option: Show steps
*May 1, 2012*

**Algebra 2**

Quadratic function: y = a x ^ 2 + b x + c has minimum or maximum in point x = - b / 2 a If a > 0 quadratic function has minimum If a < 0 quadratic function has maximum In your case : a = - 5 , b = 10 , c = 1 Function has maximum in point : - b / 2 a = - 10 / [ 2 * ( - 5...
*May 1, 2012*

**math**

The area between the graph of y = f(x) and the x-axis is given by the definite integral: A = definite integral f(x) dx from a to b
*May 1, 2012*

**math**

3 x – y = - 6 3 x + 6 = y y = 3 x + 6 4 x – 3 y = - 3 4 x - 3 ( 3 x + 6 ) = - 3 4 x - 3 * 3 x - 3 * 6 = - 3 4 x - 9 x - 18 = - 3 - 5 x - 18 = - 3 - 5 x = - 3 + 18 - 5 x = 15 Divide both sides by - 5 x = 15 / - 5 x = - 3 y = 3 x + 6 y = 3 * ( - 3 ) + 6 y = - 9 + 6 y...
*May 1, 2012*

**Algebra**

A. 6 + 9 = 15 4 ÷ 1 = 4 ( 6 + 9 ) − 1 + ( 4 ÷ 1 ) = 12 15 - 1 + 4 = 12 14 + 4 = 12 18 = 12 FALSE B. 12 ÷ 4 = 3 9 + ( 12 ÷ 4 ) = 1 9 + 3 = 1 12 = 1 FALSE C. 8 + 4 = 12 24 ÷ ( 8 + 4 ) = 24 ÷ 12 = 2 ( 16 ÷ 2 ) = 8 24 ÷...
*May 1, 2012*

**ALGEBRA**

If (5 x - 1)(x**2 + 4 x - 3) mean ( 5 x - 1 )( x ^ 2 + 4 x - 3 ) then ( 5 x - 1 )( x ^ 2 + 4 x - 3 )= 5 x * x ^ 2 + 5 x * 4 x + 5 x * ( - 3 ) - 1 * x ^ 2 - 1 * 4 x - 1 * ( - 3 ) = 5 x ^ 3 + 20 x ^ 2 - 15 x - x ^ 2 - 4 x + 3 = 5 x ^ 3 + 19 x ^ 2 - 19 x + 3
*April 30, 2012*

**ALGEBRA**

6 <= 5 - y 6 - 5 <= - y 1 <= - y Multiply both sides by -1 ______________________________________ Remark : If you multiply or divide both sides of an inequality by a negative number, you must reverse the direction of the inequality sign. ...
*April 30, 2012*

**Algebra**

- 4 x + 1 - 2 ( x - 1 ) = - 4 ( x - 4 ) - 4 x + 1 - 2 * x - 2 * ( - 1 ) = - 4 * x - 4 * ( - 4 ) - 4 x + 1 - 2 x + 2 = - 4 x + 16 - 4 x - 2 x + 1 + 2 = - 4 x + 16 - 6 x + 3 = - 4 x + 16 - 6 x + 4 x = 16 - 3 - 2 x = 13 Divide both sides by - 2 x = 13 / - 2 = - 13 / 2 x = - 6.5
*April 29, 2012*

**Math**

ð = pi
*April 29, 2012*

**Math**

A = 2 ð r h + 2 ð r ^ 2 2 ð r 10 + 2 ð r ^ 2 = 200 Divide both sides by 2 ð 10 r + r ^ 2 = 100 / ð r ^ 2 + 10 r - 100 / ð = 0 100 / ð = 31.831 Y>ou nust solve equation : r ^ 2 + 10 r - 31.831 = 0 The solutions are : 2.54 in and - 12.54 in ...
*April 29, 2012*

**Math-helpppppp**

1) P = Your polynome P / ( x -3 ) = x ^ 2 + 2 x - 5 - 3 / ( x - 3 ) Multiply both sides by ( x - 3) P = ( x ^ 2 + 2 x - 5 ) * ( x - 3 ) - 3 * ( x - 3 ) / ( x - 3 ) P = x * x ^ 2 + x * 2 x - 5 * x - 3 * x ^ 2 - 3 * 2 x - ( - 3 ) * 5 - 3 * 1 P = x ^ 3 + 2 x ^ 2 - 5 x - 3 x ^ 2...
*April 28, 2012*

**algebra 2/trig**

1) a (n ) = n ^ 3 1 ^ 3 = 1 2 ^ 3 = 8 3 ^ 3 = 27 4 ^ 3 = 64 5 ^ 3 = 125 6 ^ 3 = 216 2 ) a (n ) = n ^ 2 + 2 n 1 ^ 2 + 2 * 1 = 1 + 2 = 3 2 ^ 2 + 2 * 2 = 4 + 4 = 8 3 ^ 2 + 2 * 3 = 9 + 6 = 15 4 ^ 2 + 2 * 4 = 16 + 8 = 24 5 ^ 2 + 2 * 5 = 25 + 10 = 35 6 ^ 2 + 2 * 6 = 36 + 12 = 48
*April 28, 2012*

**MATH**

sqrt ( 6 ^ 2 + 8 ^ 2 ) = sqrt ( 36 + 64 ) = sqrt ( 100 ) = 10 ft
*April 28, 2012*

**Pre-Calculus**

1 / 5 = 0.2 1 / 198 = 0.0050505050 7 * 1 / 198 = 7 / 198 = 0. 0353535 1.23535353535 = 1 + 1 / 5 + 7 / 198 198 * 5 = 990 1 = 990 / 990 1 / 5 = 1 * 198 / 990 = 198 / 990 7 / 198 = 5 * 7 / 990 = 35 / 990 1 + 1 / 5 + 7 / 198 = 990 / 990 + 198 / 990 + 35 / 990 = 1223 / 990
*April 28, 2012*

**Pre-Calculus**

1223 / 990
*April 28, 2012*

**ALGEBRA**

What is your question ?
*April 28, 2012*

**Engineering Calculus**

If fŒ(x) > 0 at each point in an interval I, then the function is said to be increasing on I. fŒ(x) < 0 at each point in an interval I, then the function is said to be decreasing on I. In your case : fŒ(x) = 39 /( x + 6 ) ^ 2 39 positive...
*April 28, 2012*

**math**

x ^ 4 + 2 x ^ 2 - 15 = 0 Substitute : u = x ^ 2 ________________________________ Remark : If u = x ^ 2 then x ^ 4 = u ^ 2 ________________________________ You must solve equation : u ^ 2 + 2 u - 15 = 0 The exact solutions are : u = 3 and u = - 5 So solutions are : x ^ 2 = 3 x...
*April 28, 2012*

**Polynomials and quadratic application**

W = The width of fence L = Length of house = third side of fence 2 W + L = 60 ft L = 60 - 2 W A = W * L A = W * ( 60 - 2 W ) A = 60 W - 2 W ^ 2 Now you must use calculus : If a first derivative of a function at some point is equal to zero function has maxsimum or minimum. If ...
*April 28, 2012*

**Math**

4(x+y)]/(5x^2y^3) ÷ (-2x-2y)/10 = 10 * 4 ( x + y ) / [ ( 5 x ^ 2 y ^ 3 ) * ( - 2 x - 2 y ) ] = 40 ( x + y ) / [ ( 5 x ^ 2 y ^ 3 ) * - 2 ( x + y ) ] = 40 / - 2 * 5 x ^ 2 y ^ 3 ) = 40 / - 10 ( x ^ 2 y ^ 3 ) = - 4 / x ^ 2 y ^ 3
*April 27, 2012*

**Algebra**

4 k ( k + 13 ) = 13 4 k * k + 4 k * 13 = 13 4 k ^ 2 + 52 k = 13 In google type: quadratic equation online When you see list of results click on: Free Online Quadratic Equation Solver:Solve by Quadratic Formula When page be open in rectangle type: 4 k ^ 2 + 52 k = 13 and click ...
*April 26, 2012*

**math**

( a + b ) ^ 4 = a ^ 4 + 4 a ^ 3 b + 6 a ^ 2 b ^ 2 + 4 a b ^ 3 + b ^ 4 ( p ^ 2 + 3 h ) ^ 4 = ( p ^ 2 ) ^ 4 + 4 ( p ^ 2 ) ^ 3 * 3 h + 6 ( p ^ 2 ) ^ 2 * ( 3 h ^ 2 ) + 4 p ^ 2 * ( 3 h ) ^ 3 + ( 3 h ) ^ 4 = p ^ 8 + 12 p ^ 6 h + 18 p ^ 4 * 3 h ^ 2 + 4 p ^ 2 * 27 h ^ 3 + 81 h ^ 4 = p...
*April 26, 2012*

**math**

Go on: wolframalpha dot com When page be open in rectangle type: derivative (3x+2)(x^2-7) and click option = After few seconds when you see result click option: Show steps Then in rectangle type: derivative x^3+3y^2=36 and click option = After few seconds when you see result ...
*April 26, 2012*

**math**

1 m = 100 cm 1 cm = 1 / 100 m 0.1959 / 100 = 0.001959 0.1959 cm = 0.001959 m
*April 26, 2012*

**math**

( 1 / 3 ) * 24 = 24 / 3 = 8
*April 26, 2012*

**math**

2 2 / 3 = 2 + 2 / 3 = 6 / 3 + 2 / 3 = 8 / 3 10 2 / 3 = 10 + 2 / 3 = 30 / 3 + 2 / 3 = 32 / 3 2 2 / 3 / 10 2 / 3 = ( 8 / 3 ) / ( 32 / 3 ) = 3 * 8 / ( 3 * 32 ) = 8 / 32 = 8 / ( 4 * 8 ) = 1 / 4
*April 25, 2012*

**trig**

sin ( x ) = 5 / 12 cos ( x ) = + OR - sqrt [ 1 - sin ^ 2 ( x ) ] cos ( x ) = + OR - sqrt [ 1 - ( 5 / 1 3 ) ^ 2 ] cos ( x ) = + OR - sqrt ( 1 - 25 / 169 ) cos ( x ) = + OR - sqrt ( 169 / 169 - 25 / 169 ) cos ( x ) = + OR - sqrt ( 144 / 169 ) cos ( x ) = + OR - 12 / 13 In ...
*April 24, 2012*

**Algebra**

If 12 times the square root of z-1=3 times the square root 3z+1050 mean : 12 * sqrt ( z - 1 ) = 3 * sqrt ( 3 z + 1050 ) then : 12 * sqrt ( z - 1 ) = 3 * sqrt ( 3 z + 1050 ) squared both sides 12 ^ 2 * ( z - 1 ) = 3 ^ 2 * ( 3 z + 1050 ) 144 * ( z - 1 ) = 9 * ( 3 z + 1050 ) 144 ...
*April 24, 2012*